Perencanaan Pajak ( Tax Planning ) Dalam Upaya Meminimalisasi Pajak Terhutang Pph Pasal 21: Tax Planning (Tax Planning) in an Effort to Minimize Taxes Payable Pph Article 21 - Andrianto, Andrianto (Universitas Muhammadiyah Sidoarjo, 2019)
This study aimed to obtain evidence about tax planning (tax planning) in an effort to minimize the tax payable on the income tax section 21 PT. Telkom Kandatel East Surabaya. The data used in this study are primary data and Primary sekunder.Data obtained directly from interviews with management directly related to this study, while secondary data obtained from both sources other than primary data. Analysis data technique using decision theory, which is associated with the policy management in decision making.The results of the analysis in this study was obtained in the calculation of income tax article 21 methods covered employee / employer, income tax article 21 is not given in the form of benefits for employees, so that section 21 income tax paid can not be treated as expenses in calculating the lab / fiscal loss. Methods of tax allowances, income tax article 21 permanent employees paid by the company but granted in the form of income tax benefit of article 21, so it can be financed by the company in the calculation of the profit / loss fiscal. If this method raises margin Article 21 Income tax article 21 Income tax allowances that can reduce the take home pay of employees. So that income tax may be applied as a deduction in the calculation of the profit / loss tax gross-up method is used, whereby if the terms of the tax saving and take home pay is a better method